The outcome of surgical repair of Tetralogy of Fallot in KwaZulu-Natal, South Africa - Murigo-Shumba, Davidzo; Hoosen, Ebrahim GM; Bhimma, Rajendra (SA Heart Journal, 2024)
Abstract Background: Surgical repair of tetralogy of Fallot (TOF) is recommended during infancy. Late patient presentation, coupled with limited surgical and intensive care services in our setting results in late repair, potentially worsening patient outcomes. Objectives: To analyse the clinical characteristics and outcome of patients undergoing complete TOF repair at Inkosi Albert Luthuli Central Hospital (IALCH). Methods: Hospital records of all TOF patients who had complete surgical repair from January 2005 to December 2017 were analysed following ethical approval (BREC/00000476/2019). Results: 292 patients had surgical repair; most (91%) were operated at ≥12 months of age. Preoperatively, five patients had infective endocarditis, one presented with a brain abscess and one suffered a cardiac arrest from a severe hypercyanotic spell. Early mortality occurred in 15 patients (5.1%). These were associated with age at repair <12 months (p=0.017), wasting (p=0.031), prolonged cardiopulmonary bypass (p=0.004), prolonged aortic cross-clamping (p=0.001) and culture proven post-operative infection (p=0.026). Eighteen (6%) suffered major post-operative morbidities, predominantly central nervous system (CNS) complications. One hundred and eighteen (40.4%) children were lost to follow up. Conclusion: Most patients at IALCH had late repair and a significant number were lost to follow-up. Age at repair, nutritional status, duration of bypass and infections significantly influenced early mortality.